VD_FINDINFO AP / 2010 / 25 vom 13. Januar 2010 - VD Tribunal cantonal (2010)
EXCEPTIONMOYEN DE DÉFENSE, TRANSACTION JUDICIAIRE, CONCLUSIONS | 139 let. b CPC, 17 CPC, 265 al. 1 CPC, 265 al. 2 CPC, 265 CPC